2015
DOI: 10.1038/srep18527
|View full text |Cite
|
Sign up to set email alerts
|

A toxic endophyte-infected grass helps reverse degradation and loss of biodiversity of over-grazed grasslands in northwest China

Abstract: Overgrazing of China’s grasslands is increasingly causing biodiversity to decline. In degenerated grasslands of northwest China endophyte (Epichloё gansuensis) infected Achnatherum inebrians (drunken horse grass) is becoming widely distributed because of its toxicity to livestock. In this study, we investigated the ecological consequences of endophyte toxicity in this native grass, at three sites in northwest China, by comparing seed production of plant species and arthropod abundance in overgrazed grasslands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…The presence of an Epichloë endophyte in A. inebrians plants provides enhanced tolerance to abiotic stresses including drought stress (Xia et al, 2018), salt stress (Wang et al, 2018), heavy metals (Zhang et al, 2010), and low temperature (Chen et al, 2016), and as well as resistance to fungal pathogens (Xia et al, 2016) and insect pests (Zhang et al, 2012). The deterrence of grazing and the enhanced tolerance to abiotic and biotic stresses conferred by the presence of an Epichloë endophyte have led to the greatly increased distribution of A. inebrians throughout the grasslands of northwest China that have been degraded by overgrazing (Zhao et al, 2005;Yao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an Epichloë endophyte in A. inebrians plants provides enhanced tolerance to abiotic stresses including drought stress (Xia et al, 2018), salt stress (Wang et al, 2018), heavy metals (Zhang et al, 2010), and low temperature (Chen et al, 2016), and as well as resistance to fungal pathogens (Xia et al, 2016) and insect pests (Zhang et al, 2012). The deterrence of grazing and the enhanced tolerance to abiotic and biotic stresses conferred by the presence of an Epichloë endophyte have led to the greatly increased distribution of A. inebrians throughout the grasslands of northwest China that have been degraded by overgrazing (Zhao et al, 2005;Yao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A. inebrians is widely distributed in northern China and is commonly known as drunken horse grass because of its long-recognized toxic and narcotic effects on livestock, especially horses. Additionally, owing to the toxicity to livestock, recent research has shown that A. inebrians can protect biodiversity (Yao et al, 2015 ). These toxins are apparently caused by E. gansuensis (Li et al, 2004 ; Zhang et al, 2014 ).…”
Section: Alkaloidsmentioning
confidence: 99%
“…Natural land covers have been increasingly converted into urban impervious surfaces, with urban expansion exhibiting very fragmented characteristics [45,46]. The complexity of this phenomenon and its effects influence many ecological and environmental impacts, such as increased soil erosion [47], poor water quality [48], and reduced aquatic biodiversity [49], from local to global scales. The scarcity of land resource has led to the accumulation of land use conflicts over time.…”
Section: Introductionmentioning
confidence: 99%